2015
DOI: 10.7314/apjcp.2015.16.9.3835
|View full text |Cite
|
Sign up to set email alerts
|

IOTA Simple Rules in Differentiating between Benign and Malignant Adnexal Masses by Non-expert Examiners

Abstract: Objective: To evaluate the diagnostic performance of IOTA simple rules in predicting malignant adnexal tumors by non-expert examiners. Materials and Methods: Five obstetric/gynecologic residents, who had never performed gynecologic ultrasound examination by themselves before, were trained for IOTA simple rules by an experienced examiner. One trained resident performed ultrasound examinations including IOTA simple rules on 100 women, who were scheduled for surgery due to ovarian masses, within 24 hours of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
(22 reference statements)
2
14
0
1
Order By: Relevance
“…However, most studies are confined to a few groups of investigators, and the method is rarely tested by other groups for external validation, especially in other regions of the world. Our team has been studying the IOTA rules for more than eight years and has found the method to be reproducible in our population of Thai women, even among nonspecialist examiners, although performance may not be as high as reported by the pioneers.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, most studies are confined to a few groups of investigators, and the method is rarely tested by other groups for external validation, especially in other regions of the world. Our team has been studying the IOTA rules for more than eight years and has found the method to be reproducible in our population of Thai women, even among nonspecialist examiners, although performance may not be as high as reported by the pioneers.…”
Section: Discussionmentioning
confidence: 87%
“…The IOTA rules were created for clinicians to assist in the identification of ultrasound features suggesting malignancy (M‐features) or benignity (B‐features). We have found that, in our population, the IOTA rules can be used effectively by nonspecialist sonographers . Recently, the IOTA rules have increased in popularity.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our results might not necessarily be applicable to less experienced operators. However, published studies have shown that the IOTA SRs and ADNEX retain their performance in the hands of less experienced examiners [27,28,35,36,37,38,39,40,41]. This is likely to be true also for the SRR model, because the same ultrasound variables are used in the original SRs are used to calculate the risks of the SRR model.…”
Section: Discussionmentioning
confidence: 99%